2014
DOI: 10.1080/01691864.2014.884935
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional optimization of 6-DOF 3-CCC type asymmetric parallel manipulator

Abstract: In this paper, dimensional optimization of a six-degrees-of-freedom (DOF) 3-CCC (C: cylindrical joint) type asymmetric parallel manipulator (APM) is performed by using particle swarm optimization (PSO). The 3-CCC APM constructed by defining three angle and three distance constraints between base and moving platforms is a member of 3D3A generalized Stewart-Gough platform (GSP) type parallel manipulators. The dimensional optimization purposes to find the optimum limb lengths, lengths of line segments on the base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 42 publications
0
16
0
4
Order By: Relevance
“…Dexterity is one of the most important kinematic metrics used for parallel manipulators. It can be described as the capability of performing small displacement in any directions as easily as possible . Dexterity based on the condition number of the Jacobian matrix is described as κ=σminσmax where σmin and σmax are the minimum and maximum singular values of the Jacobian matrix, respectively.…”
Section: 6‐dof Gsp Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dexterity is one of the most important kinematic metrics used for parallel manipulators. It can be described as the capability of performing small displacement in any directions as easily as possible . Dexterity based on the condition number of the Jacobian matrix is described as κ=σminσmax where σmin and σmax are the minimum and maximum singular values of the Jacobian matrix, respectively.…”
Section: 6‐dof Gsp Mechanismsmentioning
confidence: 99%
“…It should be noted that κ=0 illustrates the singular configuration while κ=1 demonstrates the best configuration where the end‐effector exerts equal forces on any direction. Minimum singular values of the Jacobian matrix are also an important criterion that can be used for restricting motion of end‐effector at a minimum allowable speed .…”
Section: 6‐dof Gsp Mechanismsmentioning
confidence: 99%
“…The end points of the line segments are located on the circumferential circle of a hexagon whose corner points are labeled as A 1 A 2 , · · · ,A 5 , and A 6 . The moving platform of the mechanism is constructed by using the 6 points located on the circumferential circle of a hexagon and whose corner points were labeled as B 1 B 2 , · · · ,B 5 , and B 6 The base and moving platforms were connected to each other by using the 6 CPS type legs whose active prismatic joints were labeled as d 1 d 2 , · · · ,d 5 , and d 6 . Since the mechanism is symmetrical, the 6 × 6 inverse Jacobian matrix of this mechanism is produced by using the row vector given in Eq.…”
Section: Building Inverse Jacobian Matrices For 195 Gsp Mechanismsmentioning
confidence: 99%
“…They solved the forward kinematics and the Jacobian matrix of the new 3CCC mechanism. Toz and Kucuk [5] performed the dimensional optimization of the mechanism proposed by Gan et al [3,4] and showed that the mechanism has better dexterous workspace characteristics than the traditional GSP manipulator. Luo et al [6,7] proposed a new method for solving the forward kinematics of 4SPS-2CCS and 5SPS-1CCS mechanisms using quaternions, where S and P denote spherical and prismatic joints, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation